(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In the context of clowning acting, which historically is related to the customs and actions of each society, we propose, in this article, the following question: are we all clowns? In order to investigate this issue, we combine the analysis of Marilena Chauí (2021) about Brazilian society to our experiences with networks of women clowns, with researches, artistic performances and formative processes related to the context of clowning acting. Faced with the impossibility of identifying an affirmative answer to the question raised at the beginning of this paper, we observe that the bibliographical research recorded here is carried out by a specific scientific field of women as clowns. Besides, we demonstrate that these women are responsible for building an important, expressive and growing area of ​​contemporary knowledge about clowning.